Analisis Jaringan Antara Pengembangan Produk dan Kualitas Pelayanan dengan Kepuasan Pelanggan PT. Adhi Karya Jakarta - Ade Onny Siagian (Journal Economy and Currency Study (JECS), 2020)
This study aims to obtain information about the relationship between independent variables, namely; product development (X1) and service quality (X2) with the dependent variable, namely customer satisfaction (Y) PT. Adhi Karya Jakarta, both individually and collectively. The research instrument used was a questionnaire in the form of five answer choices. Analysis of quantitative data using two methods of analysis, namely by using frequency distribution tables and by using correlation and regression tests. In this study, there are three main conclusions, namely (1) There is a positive relationship between product development and customer satisfaction. PT. Adhi Karya Jakarta. This means that the better the product development according to the customer, the higher the customer satisfaction. Vice versa, product development is an important variable that needs to be considered in predicting customer satisfaction. (2) There is a positive relationship between service quality and customer satisfaction. PT. Adhi Karya Jakarta. This means that the higher the quality of service received by consumers, the higher customer satisfaction. Vice versa, service quality is an important variable that needs to be considered in predicting customer satisfaction. (3) There is a positive relationship between product development and service quality together with customer satisfaction of PT. Adhi Karya Jakarta concludes that the better the product development according to the customer and the higher the quality of service received by the customer, the higher the customer satisfaction. Conversely, the less good product development according to customers and the lower the quality of service received by customers, the lower customer satisfaction. This condition indicates that product development and service quality are two important variables that need to be considered in explaining increased customer satisfaction.